Dualisme Pasar Tenaga Kerja dan Dampak Upah Minimum - Mit Witjaksono (Jurnal Ekonomi dan Studi Pembangunan, 2009)
Since the introduction of the dualistic labor market by Arthur W. Lewis in the 1954, the dualism hypothesis in the segmentation of labor market is still controversy and the impact of minimum wage policy only directly positive to the highly skilled and productive workers - the best workers. This article examines critically the controvesry surrounding the impact of minimun wage policy within the context of labor market dualism in Indonesia.Keywords: labor market dualism, minimum wage policy